1998
DOI: 10.1159/000016869
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin in the Treatment of Non-Variceal Upper Gastrointestinal Bleeding

Abstract: The efficacies of somatostatin and octreotide have been widely studied in the control of bleeding from oesophageal varices. It has also been suggested that these drugs may be useful for the control of non-variceal upper gastrointestinal (UGI) bleeding, including that from peptic ulcers. In approximately 80% of patients presenting with non-variceal UGI bleeding, haemorrhage ceases spontaneously and does not recur. However, the remaining 20% of patients require active treatment. Results from recent studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 77 publications
0
14
0
1
Order By: Relevance
“…By comparison, earlier guidelines and reviews suggest that somatostatin should be effective for controlling the non-variceal upper gastrointestinal bleeding [14][15] , which is primarily attributed to the results of an early meta-analysis comparing the outcomes of somatostatin or octreotide versus H 2 antagonists or placebo for the treatment of non-variceal upper gastrointestinal bleeding [16] . But some experts argued that the trials included in the meta-analysis employed the outdated diagnostic and therapeutic approaches [17] .…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, earlier guidelines and reviews suggest that somatostatin should be effective for controlling the non-variceal upper gastrointestinal bleeding [14][15] , which is primarily attributed to the results of an early meta-analysis comparing the outcomes of somatostatin or octreotide versus H 2 antagonists or placebo for the treatment of non-variceal upper gastrointestinal bleeding [16] . But some experts argued that the trials included in the meta-analysis employed the outdated diagnostic and therapeutic approaches [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous administration of SMT or OCT decreases gastric, pyloric, duodenal, pancreatic and colonic blood flow in rats (Carlsson and Jansson, 1994). It has also been suggested that these drugs may be useful for the control of non-variceal upper gastrointestinal bleeding due to peptic ulcers (Jenkins et al, 1998;Saruc et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin (SMT) has been proposed as a treatment for variceal gastrointestinal bleeding because of its ability to decrease portal pressure without significant adverse systemic effects. The effect of somatostatin is possibly mediated through its ability to cause a splanchnic vasoconstriction and reduction of splanchnic blood flow (Carsson et al, 1994;Cerini et al, 1998;Cirera et al, 1995;Jenkins et al, 1998;Saruc et al, 2003;Sonnenberg et al, 1981). To our knowledge there are no data on the use of SMT in traumatic intra-abdominal hemorrhages.…”
Section: Introductionmentioning
confidence: 99%
“…Jenkins et al [1] review the action and application of unassociated with an ulcerating process. All of these vessels will characteristically have a start-and-stop bleeding somatostatin and its analogue, octreotide.…”
Section: Pharmacotherapy Of Acute Non-variceal Bleedingmentioning
confidence: 99%
“…The ulcer may be peptic, due to prior effect on pepsin secretion. Jenkins et al [1] have identified some of the potentially critical observations reported and thermal injury (e.g., post-polypectomy or sphincterotomy), traumatic (e.g., Mallory-Weiss tear), or neoplastic, applied these to patients with peptic ulcers: pepsin, especially pepsin 1, tends to have higher activity than in noreither benign (e.g., leiomyoma), or malignant. In patients with a Dieulafoy lesion the exposed vessel is typically mals; the proteolytic activity of pepsin 1 persists despite the high gastric pH, and fibrin clots in the laboratory bleeding and in patients with peptic ulcers.…”
Section: Pharmacotherapy Of Acute Non-variceal Bleedingmentioning
confidence: 99%